Selected Factors Affecting Uncertainty of All-Weather Microphones Research - WSZOŁEK, Grażyna (Archives of Acoustics, 2009)
Testing of devices for acoustic measurements in a free-field are being performed at the stage of designing and type certification. Free-field tests are performed only in a few laboratories - mainly in National Metrology Institutes. These are: Danish Primary Laboratory of Acoustics (DPLA, Denmark), Physikalisch Technische Bundesanstalt in Braunschweig (PTB, Germany), National Physical Laboratory (NPL, United Kingdom) National Institute of Standards and Technology (NIST, United States of America). The Vibroacoustic Laboratory of the Department of Mechanics and Vibroacoustics, AGH is the only place in Poland where this type of tests is performed. This is calibration laboratory, which has an accreditation of Polish Centre for Accreditation (AP 022). Certain factors related to the determination of frequency and directivity responses of all-weather microphones, which have a significant influence on the uncertainty of the obtained results - are presented in the paper. The response values, given below, indicate the calibration accuracy. This accuracy is necessary since the aim of the measurements is to determine corrections and designing of the proper compensating filters, which will allow to eliminate any influence of devices on the acoustic field, the parameters of which are actually under testing. This is directly related to the uncertainty assessment of environmental measurements (e.g. to the accuracy of acoustic maps). The necessity of collaboration of laboratories performing such tests and the need of inter-laboratory comparisons is pointed out in the present paper. The unification of the method of testing and the assessment of the uncertainty of results seems to be necessary.